Hemispheric asymmetry in the fusiform gyrus distinguishes Homo sapiens from chimpanzees. - Chance, SA; Sawyer, E; Clover, L; Wicinski, B; Hof, P; Crow, T (2013)
While the neural basis for linguistic communication has been linked to brain structural asymmetries found only in humans (wider connective spacing is found between the minicolumns of neurons in the left hemisphere language areas), it is unknown if the opposite microanatomical asymmetry exists in the fusiform gyrus which typically supports a right hemisphere bias for face processing. Unlike language, face processing is an ability shared with chimpanzees and, as Darwin observed, the widespread use of facial expressions in animal communication suggests a biological basis. We tested the principle that minicolumn asymmetry follows typical functional dominance in humans, and tested its evolutionary continuity, by measuring minicolumn width, neuronal size and density in the mid-fusiform cortex in 14 humans and 14 chimpanzees. We found that microanatomical asymmetry distinguishes humans from chimpanzees although the direction of asymmetry is the same as in language areas-the right hemisphere contained narrower minicolumns and smaller pyramidal neurons, as in auditory language areas. Uniformly narrow minicolumns in chimpanzees and in the human right hemisphere are consistent with mechanistic predictions supporting the apparent bias towards holistic face processing. Wider minicolumns and larger neurons in the human left hemisphere may be consistent with a language function such as word-form processing. Microanatomical asymmetry in the neocortex therefore provides a correlate of hemispheric specialisation.